Arecanut after gutkha ban: options and alternatives - Rajashekharappa, M.T.; Umesh, K.B.; Goel, Rakhi (2003)
The collapse of arecanut prices after the ban on gutkha imposed by some states has plunged farmers into a crisis and lack of export avenues has further exacerbated the situation. along with an MSP policy for arecanut to assist the beleaguered farmers, intercropping with remunerative crops can also be considered as a safeguard against income uncertainty. - Reproduced.
Keywords: Arecanut